Minimalist Interior Design and Decoration: Class Distinction in the Adaptation of Japanese Culture - Jantarangsee, Amata; Krairit, Thammachat (วารสารสังคมศาสตร์และมนุษยศาสตร์ มหาวิทยาลัยเกษตรศาสตร์, 2022)
Class distinction lies at the core of peoples’ preferences in interior design and home decoration. This paper attempts to understand the growing popularity of minimalist interior designs as a part of the social study of architecture in Thailand. Qualitative content analysis of YouTube videos about Japanese minimalist home décor is used to gain an understanding of capital accumulation and the distinctive social status of Thai minimalist houseowners. This paper begins with an attempt to understand the growing popularity of interior designs of Japanese minimalism in relation to the minimalist style home decoration trend in Thailand. This study suggests that the aesthetics of Japanese minimalism are accepted as representing good taste and promoting the distinctiveness of Thai middle-class people. The cultural and economic capital of houseowners encourage the taste of Japanese minimalist interior design. With restricted income, time, and space, the houseowners apply do-it-yourself home decoration in combination with affordability and functionality principles.